Augmenting short Cheap Talk scripts with a repeated Opt-Out Reminder in Choice Experiment surveys - Jacob Ladenburg; Søren Bøye Olsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
Hypothetical bias remains a major problem when valuing non-market goods with stated preference methods. Originally developed for Contingent Valuation studies, Cheap Talk has been found to effectively reduce hypothetical bias in some applications, though empirical results are ambiguous. We discuss reasons why Cheap Talk may fail to effectively remove hypothetical bias, especially in Choice Experiments. In this light, we suggest augmenting Cheap Talk in Choice Experiments with a so-called Opt-Out Reminder. Prior to each single choice set, the Opt-Out Reminder explicitly instructs respondents to choose the opt-out alternative if they find the experimentally designed alternatives too expensive. In an empirical Choice Experiment survey we find the Opt-Out Reminder to significantly reduce total WTP and to some extent also marginal WTP beyond the capability of the Cheap Talk applied without the Opt-Out Reminder. This suggests that rather than merely adopting the Cheap Talk practice directly from Contingent Valuation, it should be adapted to fit the potentially different decision processes and repeated choices structure of the Choice Experiment format. Our results further suggest that augmenting Cheap Talk with a dynamic Opt-Out Reminder can be an effective and promising improvement in the ongoing effort to remedy the particular types of hypothetical bias that potentially continue to invalidate Choice Experiment surveys.
Keywords: C42; C93; Q24; Q26; Q51; 330; Cheap talk; Opt-Out Reminder; Choice Experiments; hypothetical bias; stream re-establishment; opt-out effect